2020
DOI: 10.1002/anie.201913802
|View full text |Cite
|
Sign up to set email alerts
|

Combined Intrinsic and Extrinsic Proton Conduction in Robust Covalent Organic Frameworks for Hydrogen Fuel Cell Applications

Abstract: Developing new materials for the fabrication of proton exchange membranes (PEMs) for fuel cells is of great significance. Herein, a series of highly crystalline, porous, and stable new covalent organic frameworks (COFs) have been developed by a stepwise synthesis strategy. The synthesized COFs exhibit high hydrophilicity and excellent stability in strong acid or base (e.g., 12 m NaOH or HCl) and boiling water. These features make them ideal platforms for proton conduction applications. Upon loading with H3PO4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
160
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(166 citation statements)
references
References 74 publications
(38 reference statements)
3
160
0
Order By: Relevance
“…H 3 PO 4 @TPB-DMeTP-COF enables a proton flow that is even twofold compared to molten neat H 3 PO 4 (~1 × 10 -1 S cm -1 ) 25 . Note that the proton flow is significantly increased by 2-8 orders of magnitude higher than those of other analogues under anhydrous condition (Table 1) 3,5,6,10,21,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] . Meta-organic frameworks (MOFs) are hardly efficient to construct anhydrous proton-conducting systems by loading neat H 3 PO 4 into their pores.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…H 3 PO 4 @TPB-DMeTP-COF enables a proton flow that is even twofold compared to molten neat H 3 PO 4 (~1 × 10 -1 S cm -1 ) 25 . Note that the proton flow is significantly increased by 2-8 orders of magnitude higher than those of other analogues under anhydrous condition (Table 1) 3,5,6,10,21,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] . Meta-organic frameworks (MOFs) are hardly efficient to construct anhydrous proton-conducting systems by loading neat H 3 PO 4 into their pores.…”
Section: Resultsmentioning
confidence: 92%
“…These data confirmed that H 3 PO 4 @TPB-DMeTP-COF with dense and large pores enables super proton flow over a wide range of temperature. Note that a recent example of NKCOF-1 with H 3 PO 4 shows no proton conductivity under anhydrous conditions 27 . TPB-DMeTP-COF retains its crystallinity and porosity after AC impedance for 20 h ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Covalent organic frameworks (COFs), a class of crystalline porous polymers with pre‐designable pore structures, hold grand promise. [ 21–23 ] Unlike amorphous, flexible crosslinked networks, the crystalline, rigid organic frameworks of COFs are expected to afford well‐defined and stable proton‐conducting nanochannels, [ 24–30 ] as well as good water retention capability. [ 18 ] However, leveraging COF materials in the field of COF‐based PEMs for practical application remains a great challenge arising from the poor processing ability of COF materials and the poor structural integrity of COF membranes.…”
Section: Figurementioning
confidence: 99%
“…a) Temperature‐dependent proton conductivity of IPC‐COF membrane and Nafion 212 at 98% RH. b) Comparison of proton conductivity data for IPC‐COF membrane (solid stars), COF materials (open diamonds) [ 26–29,31 ] and state‐of‐the‐art PEMs (open triangles). [ 2,9,10,37–39 ] c) Proton conductivity of IPC‐COF membrane and Nafion 212 versus RH at 40 °C.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation